Educational measurement (American Council Education, 1989)
"Educational Measurement" has been the bible in its field since the first edition was published by ACE in 1951. This most recent edition of "Educational Measurement" provides extensive updates and extensions of the topics treated in the previous three editions. The volume documents progress in the field and provides critical guidance to new generations of researchers and practitioners. This work provides in-depth treatments of critical measurement topics, and the authors are acknowledged experts in their respective field